Metal status of Nairobi riverwaters and their bioaccumulation in Labeo cylindricus - Budambula, Nancy; Mwachiro, E.C. (Academic Journals, 2005)
This study focused on the analysis of metals in water and fish from Nairobi River. Water from Kikuyu, Kawangware, Chiromo, Eastleigh, Njiru and Fourteen Falls along the Nairobi River was analyzed for the presence of metals. Most of the metal levels in water were below the critical limit of World Health Organization and Kenya Bureau of Standards except for lead, chromium, iron and manganese. Isolated cases of mercury and aluminium pollution were recorded. Except for iron, sodium and potassium, there was no significant difference in the concentration of metals at different sites. This study also analyzed metal levels in fish organs and tissues of fish caught from downstream (Fourteen Falls). The highest zinc concentration (360 μg/g) was in the scales, copper recorded the highest concentration in the kidney (45 μg/g), while cadmium recorded high values (167 μg/g) in the heart. Lead recorded high values (178 μg/g) in the heart and mercury recorded high values also in the heart (1000 ng/g). Most of these organs, are however, not eaten by man as food. Although metal levels were within normal levels in the water at Fourteen Falls, mercury, copper, lead and iron recorded higher than accepted levels in some fish organs. This calls for caution in the consumption of fish from Fourteen Falls.
Keywords: bioaccumulation; fish; Fourteen Falls; metal; Nairobi River; pollution